Asuransi dalam Perspektif Hukum Islam - muhammad muhammad (Jurnal Hukum IUS QUIA IUSTUM, 2001)
Since takaful has been operated as a finance and insurance institution in which the investation directed to any legal sectors and themutual sharing profit determined by two sides, it can be judged that this special system would not break out the islamic economical principles.